2008
DOI: 10.1111/j.1442-8903.2008.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

Some practical suggestions for improving engagement between researchers and policy‐makers in natural resource management

Abstract: Policy-makers and managers in natural resource management (NRM) often complain that researchers are out of touch. Researchers often complain that policy-makers and managers make poorly informed decisions. In this article, we report on a meeting between researchers, policy-makers and managers convened to identify practical solutions to improve engagement between these camps. A necessary starting point is that every researcher and policy-maker should understand, and tap into, the motivations and reward systems o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
141
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(143 citation statements)
references
References 5 publications
2
141
0
Order By: Relevance
“…Whilst research faculty tenure and promotion at most academic institutions are generally dependent on excellence in research, teaching, and service, implementation of research recommendations, including conservation, is generally not linked with job security and advancement. Though some institutions are increasingly valuing service learning and societal contributions in the tenure and promotion process (June 2013), there have traditionally been disincentives within academia for cross-disciplinary research and its applications in conservation (Arlettaz et al 2010, Gibbons et al 2008Knight et al 2008). This is definitely the case in Mexico, where the National Council of Science and Technology (CONACYT) can make substantial contributions to top researchers' incomes based on research productivity, defined in terms of publications and grants (Altbach 2015).…”
Section: Promoting An Enabling Environment For Fsa Site Protectionmentioning
confidence: 99%
“…Whilst research faculty tenure and promotion at most academic institutions are generally dependent on excellence in research, teaching, and service, implementation of research recommendations, including conservation, is generally not linked with job security and advancement. Though some institutions are increasingly valuing service learning and societal contributions in the tenure and promotion process (June 2013), there have traditionally been disincentives within academia for cross-disciplinary research and its applications in conservation (Arlettaz et al 2010, Gibbons et al 2008Knight et al 2008). This is definitely the case in Mexico, where the National Council of Science and Technology (CONACYT) can make substantial contributions to top researchers' incomes based on research productivity, defined in terms of publications and grants (Altbach 2015).…”
Section: Promoting An Enabling Environment For Fsa Site Protectionmentioning
confidence: 99%
“…There is a need to manage, through negotiation, the boundaries between the producers of knowledge (researchers) and the executors of action (policy-makers) (Van Kerkhoff and Lebel, 2006). It is recommended that researchers and policymakers should understand and take into account into each other's motivations and reward systems (Gibbons et al, 2008). Researchers also need to understand and target the world of institutions, policies and politics (Pierce et al, 2005), as well as the processes of decision-making, behaviour change and value transfer (Reyers et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…5 One approach to increasing the interaction or improving the interface between researchers and policy makers is use of secondments. 6,7,8 Secondments have been used in the healthcare setting as a way to bring an individual's expertise to a team, and to develop staff knowledge and skills. Previous research has found that secondments involving researchers and healthcare practitioners are an efficient way to transfer research.…”
Section: Introductionmentioning
confidence: 99%